The effect of pre-exercise hyperhydration on exercise performance, physiological outcomes and gastrointestinal symptoms: a systematic review - Jardine, W. T.; Aisbett, B.; Kelly, M. K.; Burke, L. M.; Ross, M. L.; Condo, D.; Périard, J. D.; Carr, A. J. (Sports Medicine, 2023)
Background: Fluid loss during prolonged exercise in hot conditions poses thermoregulatory and cardiovascular challenges for athletes that can lead to impaired performance. Pre-exercise hyperhydration using nutritional aids is a strategy that may prevent or delay the adverse effects of dehydration and attenuate the impact of heat stress on exercise performance. Objectives: The aim of this systematic review was to examine the current literature to determine the effect of pre-exercise hyperhydration on performance, key physiological responses and gastrointestinal symptoms. Methods: English language, full-text articles that compared the intervention with a baseline or placebo condition were included. An electronic search of Medline Complete, SPORTDiscus and Embase were used to identify articles with the final search conducted on 11 October 2022. Studies were assessed using the American Dietetic Association Quality Criteria Checklist. Results: Thirty-eight studies involving 403 participants (n = 361 males) were included in this review (n = 22 assessed exercise performance or capacity). Two studies reported an improvement in time-trial performance (range 5.7-11.4%), three studies reported an improvement in total work completed (kJ) (range 4-5%) and five studies reported an increase in exercise capacity (range 14.3-26.2%). During constant work rate exercise, nine studies observed a reduced mean heart rate (range 3-11 beats min-1), and eight studies reported a reduced mean core temperature (range 0.1-0.8 °C). Ten studies reported an increase in plasma volume (range 3.5-12.6%) compared with a control. Gastrointestinal symptoms were reported in 26 studies, with differences in severity potentially associated with factors within the ingestion protocol of each study (e.g. treatment, dose, ingestion rate). Conclusions: Pre-exercise hyperhydration may improve exercise capacity during constant work rate exercise due to a reduced heart rate and core temperature, stemming from an acute increase in plasma volume. The combination of different osmotic aids (e.g. glycerol and sodium) may enhance fluid retention and this area should continue to be explored. Future research should utilise valid and reliable methods of assessing gastrointestinal symptoms. Furthermore, studies should investigate the effect of hyperhydration on different exercise modalities whilst implementing a strong level of blinding. Finally, females are vastly underrepresented, and this remains a key area of interest in this area.